Cytologic findings of gastric schwannoma: A case report. Issue 2 (31st August 2012) - Rodriguez, Erika; Tellschow, Steven; Steinberg, David M.; Montgomery, Elizabeth
<x xml:space="preserve">Abstract</x> Spindle cell lesions of the stomach are rare. They usually affect the submucosa or muscularis propria and therefore can be sampled by endoscopic fine needle aspiration. The most common tumor in this category is gastrointestinal stromal tumor (GIST), followed by leiomyoma and gastric schwannoma. Gastric schwannoma is a benign tumor of neuroectodermal origin that has overlapping morphologic/cytologic features with GIST and leiomyoma. Gastric schwannomas differ from peripheral schwannomas by lacking a capsule, Verocay bodies, Antoni B areas, and thick‐walled vessels. They are characterized morphologically by poorly defined borders, cuffs of lymphoid tissue and a haphazard spindle cell proliferation. We present here the cytologic and histopathologic features of a gastric schwannoma. The tumor was composed of spindle cells with delicate eosinophilic cytoplasm and wavy nuclei, with an associated conspicuous lymphoid backdrop. The latter feature raised the possibility of a lymphoid lesion, a problem cytopathologists should be aware of. Diagn. Cytopathol. 2014;42:177–180. © 2012 Wiley Periodicals, Inc.